Automated car parking system with increased security by digital image processing - Chowdhury, Md. Tanzir; Rahman, Sheikh Ashik; Islam, Md. Fahad; Mallick, Md. Rezwan (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.